Deep Penetration of Kelps Offshore Along the West Coast of Greenland - Krause-Jensen, Dorte; Sejr, Mikael K.; Bruhn, Annette; Rasmussen, Michael B.; Christensen, Peter Bondo; Hansen, Jørgen L. S.; Duarte, Carlos M.; Bruntse, Grethe; Wegeberg, Susse (Frontiers in Marine Science, 2019)
Until recently, Arctic kelp forests were so understudied that they did not even appear in global kelp forest maps. An increasing focus on Arctic coastal ecosystems has documented extended kelp forests along Arctic coastlines but the distribution of the forests is still not well documented and opens up for surprises. Here we report kelp depth limits deeper than 61 m (median: 38.4 m, 10-90% percentiles: 10.8-54.4 m) in the Disko Bay region, Greenland, at latitudes of 67-70°N. We compiled, for comparison, existing records of kelp depth limits in high latitude (50°N) regions (median: 17.7 m, 10-90% percentiles: 9.0-38.1 m), which underline that the Disko Bay kelps hold a depth-record for this region. The deepest kelps were located at offshore sites beyond the Disko Island and the main coast. The clear waters offshore with euphotic zones (1% of surface irradiance) extending to 67 m depth provide, along with deep rocky seafloors and low density of sea urchins, the basis for these deep kelps. The sites were ice-covered for 77-133 days yr-1, which is beyond the length of the polar night (30-60 days yr-1) in the region, suggesting a potential for further depth penetration of kelp forests in a future with longer open water periods and more light potentially reaching the seafloor.